RELIABILITY AND SIMPLE FAILURE PROBABILITY OF TWO PILE CAPS REINFORCED CONCRETE: : CASE STUDY (Revista Brasileira Multidisciplinar, 2023)
Current Brazilian design codes indicate the design of reinforced concrete structures according to Limit States Method, using global and partial safety factors, without specifying a reliability study and calculation of the probability of failure. Several authors indicate that the reliability study is necessary to assess the safety of structures, and these concepts have already been incorporated by foreign codes. Engineering is a risky activity and using statistics to address the randomness of variables is the modern trend. This paper aims to perform a reliability study of two pile caps reinforced concrete in a simple and practical way working with two random variables: load and resistance. It was proposed different ways to assemble the load and resistance curves. The reliability and the probability of failure of each case were calculated. It was observed that the reliability and the probability of failure are dependent on the compressive strength of the concrete and its rigor in the condition of preparation.
Keywords: Reliability. Probability of failure. Safety. Pile-Caps. Reinforced concrete. Design.